PREVENTION MEASURES IN THE SYSTEM OF PROCEDURE FORCED MEASURES (Journal of actual problems of jurisprudence, 2019)
The article considers the preventive measures in the system of measures of procedural coercion. The implementation of criminal procedure is often associated with the use of coercion by citizens of the state involved in criminal proceedings to engage in criminal proceedings. In a number of cases, participants in the process and other subjects impede the investigation and resolution of criminal cases by non-fulfillment of procedural obligations, as well as the commission of actions that violate the procedure of the case. To ensure the normal course of the investigation, the law provides for a system of measures of criminal procedural coercion.Measures of criminal procedural coercion are provided for by the Criminal Procedure Code of the Republic of Kazakhstan as a coercive means applied by the inquiry body, investigator, prosecutor and court to the accused (suspect), the victim, the witness and other subjects of the court proceedings in order to prevent or repress their unlawful behavior, obtaining evidence as well as securing a civil action.The measures of criminal procedural coercion are not identical in nature, their application has different goals. A variety of measures of criminal procedural coercion are preventive measures.Measures of restraint are measures of procedural coercion provided for by law, applied in accordance with the procedure established by law by the inquiry body, the investigator, the prosecutor and the court in relation to the accused (convicted) and, in exceptional cases, the suspects, who consist in limiting the freedom of these persons ) in order to ensure their participation in legal proceedings and to prevent their possible attempts to escape from the investigation and the court, to prevent the establishment of the truth in the case or the execution of the sentence, to lie criminal activity.Key words: measures of procedural coercion, classification of measures of restraint, suspect, accused, convict, detention, house arrest.